EFFECTIVENESS OF NEARPOD DIGITAL INTERACTIVE MEDIA IN SOCIAL STUDIES LEARNING ON MOTIVATION AND COGNITIVE OUTCOMES - Adela Putri Rahmadani; Nur Isroatul Khusna (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Digital transformation in education requires learning that is no longer teacher-centered, but actively involves students through the use of interactive media. In social studies learning, especially in abstract and conceptual history material, conventional methods often result in low learning interest and limited cognitive abilities among students. This condition encourages the need for innovative learning media that can present material in a visual, participatory, and meaningful way. One digital media that has these characteristics is the Nearpod application. This study used a quantitative approach with a nonequivalent control group design involving seventh-grade students at an Islamic junior high school in Blitar as research subjects. Data were obtained through learning interest questionnaires and cognitive ability tests, then analyzed using independent sample t-tests, MANOVA, and N-Gain calculations. The results of the analysis show that there is a significant effect of using Nearpod on increasing students' learning interest and cognitive abilities, both partially and simultaneously, with a very strong effect size, producing a significance value of 0.000, which is below the significance level of 0.05. The strength of this effect was reinforced by the Partial Eta Squared effect size calculation of 0.921, which is classified as a very strong effect. The N-Gain value for cognitive abilities was in the high and effective category, indicating an optimal increase in mastery of the material. These findings confirm that the use of Nearpod interactive digital learning media contributes positively to improving the quality of the social studies learning process and outcomes. ABSTRAK Transformasi digital dalam dunia pendidikan menuntut pembelajaran yang tidak lagi berpusat pada guru, tetapi mampu melibatkan siswa secara aktif melalui pemanfaatan media interaktif. Dalam pembelajaran Ilmu Pengetahuan Sosial, khususnya pada materi sejarah yang bersifat abstrak dan konseptual, metode konvensional masih sering menimbulkan rendahnya minat belajar serta keterbatasan kemampuan kognitif siswa. Kondisi tersebut mendorong perlunya inovasi media pembelajaran yang mampu menyajikan materi secara visual, partisipatif, dan bermakna. Salah satu media digital yang memiliki karakteristik tersebut adalah aplikasi Nearpod. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi eksperimen tipe nonequivalent control group design yang melibatkan siswa kelas VII madrasah tsanawiyah yang ada di kota blitar sebagai subjek penelitian. Data diperoleh melalui angket minat belajar dan tes kemampuan kognitif, kemudian dianalisis menggunakan uji independent sample t-test, MANOVA, serta perhitungan N-Gain. Hasil analisis menunjukkan adanya pengaruh signifikan penggunaan Nearpod terhadap peningkatan minat belajar dan kemampuan kognitif siswa, baik secara parsial maupun simultan, dengan ukuran efek yang tergolong sangat kuat, yakni menghasilkan nilai signifikansi sebesar 0,000 yang berada di bawah taraf signifikansi 0,05.Kekuatan pengaruh tersebut diperkuat perhitungan effect size uji Partial Eta Squared sebesar 0,921 yang termasuk dalam kategori pengaruh sangat kuat Nilai N-Gain kemampuan kognitif berada pada kategori tinggi dan efektif, yang mengindikasikan terjadinya peningkatan penguasaan materi secara optimal. Hasil penelitian ini menegaskan bahwa pemanfaatan media pembelajaran digital interaktif Nearpod berkontribusi positif dalam meningkatkan kualitas proses dan hasil pembelajaran IPS.